Determinación de secuestro de carbono en cuatro especies forestales a un año de establecimiento en suelos degradados en trópico húmedo Yurimaguas 2022 - Torres Soberon, Ramiro (2025)
The study was conducted in for communities of the Yurimaguas District, Loreto Region, with the purpose of evaluating carbon sequestration of four forest species in degraded soils in the Wet Tropics of the Peruvian Amazon. The evaluated forest species were paliperro (Miconia barbeyana), tahuarí (Tabebuia serratifilia), capirona (Calycophyllum spruceanum), and marupa (Simarouba amara), all one-year-old, distributed in eight plots located in different populated centers of the area. Measurements of tree height and diameter at breast height (DBH) of 1600 individuals were recorded to estimate biomass and carbon sequestration using allometric equations. The results showed significant differences (p < 0.05) among the evaluated species regarding DBH, height, biomass, and stored carbon. Specifically, the Marupa species recorded the highest DBH value (4.8 cm), while Tahuari stood out for its greater height (6 m). In terms of biomass and stored carbon, tahuarí obtained the highest values (1660 kg/ha), followed by marupa (894 kg/ha), capirona (225 kg/ha), and paliperro (150 kg/ha). These findings suggest that plantation production systems contribute to the conservation and regeneration of degraded ecosystems, providing a solid foundation for future more comprehensive studies with other forest species at different growth stages and soil conditions.